2020
DOI: 10.3892/etm.2020.9357
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑124 regulates cell pyroptosis during cerebral ischemia‑reperfusion injury by regulating STAT3

Abstract: Cerebral ischemia-reperfusion injury (CIRI) is the observed continuation and deterioration of ischemic injury, and currently, there are no effective treatment strategies for the condition. It has been reported that microRNAs (miRNAs) serve an important role in CIRI by regulating pyroptosis. The present study demonstrated that miRNA-124 regulated CIRI by regulating STAT3. To explore the relationship between miRNA-124/STAT3 and pyroptosis in CIRI, CIRI was simulated using a middle cerebral artery occlusion model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…3,4 This part of aberrantly expressed miRNAs are mainly involved in the regulation of the occurrence and development of CIRI by affecting life activities such as energy metabolism, apoptosis, ROS production and secretion of inflammatory cytokines IL-6 and TNF-α. 5,6 Our previous gene analysis found that the expression of miR-26b-5p was downregulated in the infarcted brain tissue of cerebral ischemia-reperfusion rats, which was consistent with the results of another gene chip analysis. 7 Recently, microarray analysis of mouse cerebral artery ischemia model showed that miR-26b-5p was downregulated in CIR brain tissue.…”
Section: Introductionsupporting
confidence: 86%
“…3,4 This part of aberrantly expressed miRNAs are mainly involved in the regulation of the occurrence and development of CIRI by affecting life activities such as energy metabolism, apoptosis, ROS production and secretion of inflammatory cytokines IL-6 and TNF-α. 5,6 Our previous gene analysis found that the expression of miR-26b-5p was downregulated in the infarcted brain tissue of cerebral ischemia-reperfusion rats, which was consistent with the results of another gene chip analysis. 7 Recently, microarray analysis of mouse cerebral artery ischemia model showed that miR-26b-5p was downregulated in CIR brain tissue.…”
Section: Introductionsupporting
confidence: 86%
“…Gastrodin regulated the miR-22/NEAT1 axis and reduced the pro-inflammatory cytokines, reducing pyroptosis and attenuating the I/R injuries both in vivo and in vitro (Zhang et al, 2021a). MiR-124, which was previously discussed for apoptosis and was described as a marker of I/R injury, inhibits STAT3 expression and thereby reduces pyroptosis and improves the neurological outcome (Sun et al, 2020a). Overall, more studies are needed in order to fully elucidate how miRNAs regulation is related to pyroptosis and how these could potentially be used as therapeutic targets.…”
Section: Pyroptosismentioning
confidence: 92%
“…Meanwhile, microRNAs are a class of small non-coding RNAs that play a significant role in various biological processes related to cell death. A recent study has suggested that microRNA-124 inhibits pyroptosis induced by cerebral I/R injury by regulating the STAT3 signaling pathway [ 58 ]. Furthermore, it has been suggested that ginsenoside Rd could attenuate cerebral I/R injury by exerting an anti-pyroptotic effect via the miR-139-5p/Keap1/Nrf2 axis [ 59 ].…”
Section: Pyroptosis and I/r Injurymentioning
confidence: 99%